CARDIOVASCULAR RISK IN PATIENTS WITH CHRONIC OBSTRUCTIVE PULMONARY DISEASE - L.I. Konopkina; L.A. Botvinikova; M.A. Krykhtina (Проблеми екології та медицини)
Chronic obstructive pulmonary disease (COPD) has many risk factors (RF) and pathogenetic mechanisms that are common with cardiovascular diseases (CVD), especially coronary heart disease (CHD). Among the most widespread shared risk factors are smoking, age and physical inactivity caused by respiratory failure, poor nutrition, and environmental deterioration. The aim of our study was to assess the degree of total cardiovascular risk (CVR) in patients with COPD of severe course for prediction of their cardiovascular events and justify the ways of total CVR correction for each of patients. We observed 29 men with the severe course of COPD in stable phase of the pathological process. In order to identify the extent of total CVR, we determined the demographic parameters for each patient (age, gender), attitude to smoking (smoker / non-smoker), systolic blood pressure and total cholesterol (TC) levels (mmol/l). The results generally showed that the estimate of total CVR in patients with COPD is crucial when choosing the prevention strategy aimed at overcoming a particular emergency, including the optimization of nutrition, increased activity, as well as the prescription of adequate antihypertensive and lipid-lowering therapy.